Reproduction of Poplars by Seed-Nursery Trials - Mathur, R. S.; Sharma, K. K.; Sood, D. P. (Indian Forester, 1983)
Seeds of P. deltoides comprising 10 stands were imported from U.S.A. as part of introduction programme, Different germination medium, type of containers and conditions were tried to obtain higher survivals. The germination medium i.e. two parts soil and one part river sand duly sterilized proved most effective and gave the higher survivals and best shoot development. Enamel trays proved the best container for sowing, poplar seeds. For the first time a break through in raising seedlings of exotic Populus species from seed has been achieved. Individual plants within stands and between stands of P. deltoides showed a wide variation in shoot development indicating a hope for selection of superior individuals for afforestation programmes.